CD4–HIV-1 Envelope Interactions: Critical Insights for the Simian/HIV/Macaque Model - Sharma, Amit (AIDS Res Hum Retroviruses, 2018)
The macaque models of HIV-1 infection have been a cornerstone of research on transmission, pathogenesis, and prevention. In particular, the infection of macaques with chimeric simian/HIV-1 viruses (SHIVs) is central to the vaccine development pipeline because SHIVs encode the key target of HIV-1-neutralizing antibodies, the HIV-1 envelope (env) protein. In this review, we highlight some of the recent studies that have improved our understanding of the CD4–HIV-1 env interaction, which are crucial for development of SHIV/macaque models of HIV-1 infection.